Do the Framing Effect Occur in the Investment Decision Based on Tabular Format Information Risk: A Fuzzy-Trace Theory Framework? - Negina Kencono Putri; Zaki Baridwan; Supriyadi Supriyadi; Ertambang Nahartyo (The Indonesian Journal of Accounting Research, 2014)
Abstract: This study tests on investment decisions based on risk information within the framework of verification Fuzzy Trace Theory (FTT). FTT assumes individuals prefer to use the simple reason that in the presentation of information and make a decision. An experiment which involved 27 participants was conducted. The experiments carried out to test whether the risk information of different frame-sequential time given concerning the framing effect described through the framework of FTT-can affects investment decision-making process. The results showed that the participants in this study chose to perform actions that are not at risk when information is presented in a positive frame. Investment decisions which they set such decisions tend to avoid risk. This is consistent with FTT are focusing testing on the frame problem. Other findings obtained in this study in the form of the tendency of the experimental participants to take risky decisions when information is presented in a negative frame. Abstrak: Penelitian ini berutjuan untuk menguji keputusan investasi berbasis risiko dalam kerangka Fuzzy Trace Theory (FTT). FTT mengasumsikan bahwa seseorang memiliki preferensi untuk menggunakan informasi yang ditamilkan dalam bentuk yang sederhana dalam membuat sebuah keputusan. Penelitian ini merupakan penelitian eksperimen yang melibatkan 27 orang partisipan. Eksperimen yang dilakukan menguji apakah informasi risiko yang dibingkai secara berbeda dan disampaikan dalam waktu yang berurutan dalam kerangka FTT akan mempengaruhi proses pembuatan keputusan investasi Hasil penelitian menunjukkan bahwa partisipa dalam penelitian ini memilih untuk mengambil keputusan yang tidak berisiko bila informasi disampaikan dalam frame yang positif. Hasil lain yang diperoleh dalam penelitian ini adalah bahwa seseorang cenderung untuk mengambil keputusan yang berisiko apabila informasi disampaikan dalam frame yang negatif.